Production, analysis of use and financing biogas projects - Marković Sanja (Trendovi u Poslovanju)
The growth of the global economy and population at global level has resulted in enormous consumption of fossil fuels, environmental pollution, increased greenhouse gas emissions and evident climate changes. In the context of the global initiative for more intensive uses of renewable energy sources (RES), in the middle of the last century, the increasing use of biogas began, especially in rural areas of China and India (direct use for cooking and lighting). At the end of the last century, in Europe biogas was used in cogeneration biogas plants (which combined heat and power production), supplying (injectioning) the natural gas network for vehicle powering or for fuel cells. In order to stimulate investments in the field of RES, the Government of the Republic of Serbia has adopted the Regulation on Incentive Measures for the Production of Electricity from the RES and issued a Guide for Investors on the Construction of Plants and Production of Electricity / Heat from Biomass. In addition to the use of biogas with a range of socioeconomic and environmental benefits, the increasingly stringent emission limit values for greenhouse gases in the atmosphere, which requires the use of increasingly advanced technologies, gives priority to the use of biogas as an RES.